Application research on distributed Zabbix network monitoring system - Xiao-hui GUO; Run-zhi LI; Qian ZHANG; Zong-ming WANG (Tongxin xuebao)
With the increasing number of server,to ensure the normal operation of the server and application services becomes more and more complex.The importance of server monitoring system in modern server management was explained.With Zabbix,a distributed monitoring and control system was deployed,realizing some important application services monitoring in Windows and Linux environment with distributed network monitor and control system.The principle and configuration of the monitoring of Web Server,Database and DNS Server were introduced.Finally,the use cases using in the network center were shown.